Taxonomic and phylogenetic census of the Celastrales: A synthetic review - D.A. Patil2, Shisode S.B.1 and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">A comprehensive assessment of the taxonomic and phylogenetic status of the celeastralean plexus is presented. An attempt has been made to review synthetically based on the data from different disciplines divulged by earlier authors and from present authorÃ¢â‚¬â„¢s study on the alliance. The taxonomic literature indicated that the Celeastrales (sensu lato) are a loose-knit assemblage. The tribal, subfamilial, familial and even ordinal boundaries are uncertain and even criss-cross each other. It appeared that the alliance can be grouped under two taxonomic entities viz., the Celastrales and the Rhamnales which appear evolved convergently.